Investigating the determinants of working capital in the Gulf Cooperation Council - Bashar Abu Khalaf (17541639) (2023)
This study aims to identify the determinants affecting the working capital of non-financial companies listed on the Gulf Cooperation Council (GCC). All non-financial companies listed on Qatar, Oman, Saudi Arabia, United Arab Emirates, Bahrain, and Kuwait were collected and resulted in a total of 532 companies during the period of 2008–2021. The final sample included 135 companies (25.38 percent of the total number of non-financial companies in the GCC) that had at least 10 years of data out of the 14 years. This paper applied the panel regression (random and fixed effects techniques); the insignificant result of the Hausman test favored the random effect results. The results argued that there is a negative significant effect of leverage, profitability, and firm size on working capital. This suggests that high-leveraged companies tend to have less working capital and this is due to the commitment to servicing the debts. In addition, large companies tend to have less working capital since they have huge expenses to pay and this affects negatively their working capital level. Also, an interesting result is that highly profitable companies tend to have less working capital since they include themselves in more projects. While, there is a positive significant effect of growth and cash flow on working capital, which confirms that high-growth companies tend to have better working capital. Other Information Published in: Journal of Governance and Regulation License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.22495/jgrv12i3art1